Literatur Review: Pengaruh Intensitas Modal, Keputusan Investasi, dan Agresivitas Pajak terhadap Nilai Perusahaan - Nur Laila Choiru Nisa; Chaerunnisa Andriani; Nugroho Heri Pramono (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
Company value is an important indicator that reflects company performance and investor perceptions of future business prospects and sustainability. Various strategic decisions made by management, such as capital intensity management, investment decisions, and tax aggressiveness policies, play a significant role in shaping company value. This study aims to examine and analyze the effect of capital intensity, investment decisions, and tax aggressiveness on company value through a literature review approach. The method used is a literature review by examining various relevant national and international scientific articles obtained from academic databases such as Google Scholar, Publish or Perish, and SINTA. The results of the study show that capital intensity has a positive effect on company value because it reflects long-term production capacity and operational efficiency. Investment decisions have also been proven to have a positive effect on company value because they signal management's optimism about future growth prospects. Meanwhile, tax aggressiveness can increase company value through tax savings and increased cash flow, but it has the potential to cause reputational and governance risks if done excessively. Overall, the reviewed literature shows that these three variables have an impact on company value, with the caveat that optimal and transparent management is necessary. This study is expected to serve as a reference for further research and as a consideration for company management and investors in making strategic decisions.